2023
DOI: 10.3389/fbioe.2023.1092361
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid design and modelling of a customised graded Ti-6Al-4V porous hip implant to reduce stress-shielding: An experimental and numerical analysis

Abstract: Stress shielding secondary to bone resorption is one of the main causes of aseptic loosening, which limits the lifespan of hip prostheses and exacerbates revision surgery rates. In order to minimise post-hip replacement stress variations, this investigation proposes a low-stiffness, porous Ti6Al4V hip prosthesis, developed through selective laser melting (SLM). The stress shielding effect and potential bone resorption properties of the porous hip implant were investigated through both in vitro quasi-physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
(105 reference statements)
1
30
0
Order By: Relevance
“…This indicates that axial gradient stiffness increases stress in the medial regions of the femur, consistent with the results reported by recent studies on porous femoral stems. 11,12,14,22 Bone loss was more concentrated in Gruen zone 7 near the lesser trochanter region of the femur, 23,24 and the results showed that DAGS Gyroid has maximum stress transfer in the proximal medial section. Maximum stress shielding reduction is 14.42% in Gruen zone 6 and 13.37% in Gruen zone 7 for DAGS Gyroid design, according to Figure 5.…”
Section: Stress Shielding and Stress Transfermentioning
confidence: 94%
“…This indicates that axial gradient stiffness increases stress in the medial regions of the femur, consistent with the results reported by recent studies on porous femoral stems. 11,12,14,22 Bone loss was more concentrated in Gruen zone 7 near the lesser trochanter region of the femur, 23,24 and the results showed that DAGS Gyroid has maximum stress transfer in the proximal medial section. Maximum stress shielding reduction is 14.42% in Gruen zone 6 and 13.37% in Gruen zone 7 for DAGS Gyroid design, according to Figure 5.…”
Section: Stress Shielding and Stress Transfermentioning
confidence: 94%
“…This investigation involves fixed flexion angles ranging from 8 to 121 and abduction angles ranging from 6 to 12 degrees. [33][34][35][36][37][38][39][40][41][42][43][44][45] The loading condition plays a significant role in assessing the performance of hip implants. However, the mechanical performance of a hip implant stem within an implanted femur bone was evaluated following ISO-7206-08 guidelines in recent literature.…”
Section: Experimental Methods and Boundary Conditions For Assessing H...mentioning
confidence: 99%
“…In those works, the analysis involved applying axial loads ranging from 600 N to 5 KN on the femoral head. 15,16,33,35,[37][38][39][41][42][43][46][47][48][49][50] In numerous recent studies, dynamic load component values have been utilized to assess the mechanical behaviour of hip implant stems within implanted bones. 12,34,43,45,47,[51][52][53] However, a German study group known as ''Orthoload'' has released dynamic force and moment data of daily activities in various environments.…”
Section: Experimental Methods and Boundary Conditions For Assessing H...mentioning
confidence: 99%
See 2 more Smart Citations